Understanding macromolecules formation from the catalytic hydroconversion of pyrolysis bio-oil model compounds. (December 2016) - Ozagac, M.; Bertino-Ghera, C.; Uzio, D.; Rivallan, M.; Laurenti, D.; Geantet, C.
Abstract: Catalytic hydroconversion of pyrolysis bio-oils is a promising process that can greatly contributes to their deoxygenation. Other simultaneous reactions such as condensation or oligomerization leading to heavy molecular weight compounds are detrimental to the process and still not well understood. This study deals with the hydroconversion ofD -glucose and furfural in a batch reactor with a NiMo/alumina catalyst. Considering the carbon balances and SEC-RI analysis of hydroconversion products, we describe fast reaction pathways leading to soluble macromolecules (up to 700 g mol −1 ) that are further precipitated into the solid phase. From theD -glucose conversion, 13 C NMR analysis of residues revealed significant amounts of aromatic carbons. Also detected by FTICR-MS analysis of a liquid effluent, those structures were likely formed through dehydration reactions. Finally, a high water content in the feed demonstrated thatD -glucose was preserved from dehydration reactions contrary to furfural which is prone to be hydrolyzed into soluble macromolecules precursors. Graphical abstract: Highlights: Catalytic hydroconversion ofD -glucose and furfural have been performed. Furfural hydration andD -glucose dehydration lead to high molecular mass molecules. Characterization of soluble macromolecules by SEC-RI/UV and FTICR-MS. Water limitsD -glucose dehydration and high molecular mass molecules precipitation.